Unveiling the Differences of Secretome of Human Bone Marrow Mesenchymal Stem Cells, Adipose Tissue-Derived Stem Cells, and Human Umbilical Cord Perivascular Cells: A Proteomic Analysis - Pires, Ana O; Mendes-Pinheiro, Barbara; Teixeira, Fábio G; Anjo, Sandra I; Ribeiro-Samy, Silvina; Gomes, Eduardo D; Serra, Sofia C; Silva, Nuno A; Manadas, Bruno; Sousa, Nuno; Salgado, Antonio J (Stem cells and development, 2016)
The use of human mesenchymal stem cells (hMSCs) has emerged as a possible therapeutic strategy for CNS-related conditions. Research in the last decade strongly suggests that MSC-mediated benefits are closely related with their secretome. Studies published in recent years have shown that the secretome of hMSCs isolated from different tissue sources may present significant variation. With this in mind, the present work performed a comparative proteomic-based analysis through mass spectrometry on the secretome of hMSCs derived from bone marrow (BMSCs), adipose tissue (ASCs), and human umbilical cord perivascular cells (HUCPVCs). The results revealed that BMSCs, ASCs, and HUCPVCs differed in their secretion of neurotrophic, neurogenic, axon guidance, axon growth, and neurodifferentiative proteins, as well as proteins with neuroprotective actions against oxidative stress, apoptosis, and excitotoxicity, which have been shown to be involved in several CNS disorder/injury processes. Although important changes were observed within the secretome of the cell populations that were analyzed, all cell populations shared the capability of secreting important neuroregulatory molecules. The difference in their secretion pattern may indicate that their secretome is specific to a condition of the CNS. Nevertheless, the confirmation that the secretome of MSCs isolated from different tissue sources is rich in neuroregulatory molecules represents an important asset not only for the development of future neuroregenerative strategies but also for their use as a therapeutic option for human clinical trials.